EzDubs.ai Application to Assist University Students Understand Spoken Discourse from German Videos - Pramesti, Revalina Agdya; Bukhori, Herri Akhmad (Universitas Negeri Malang, 2024)
This study aims to describe the application of EzDubs.ai to assist university students understand spoken discourse in German videos and to find out university students' responses to the application of this platform. The method used in this research was descriptive qualitative with three stages of data processing according to Miles and Hubermann, namely, data reduction, data presentation, and conclusion drawing. The data collection techniques in this study were observation and questionnaires and the instruments used in this study were observation sheets and questionnaire sheets. The data sources used in this study were 52 students from offering A, B, and C Class of 2022 German Language Education Study Programme, Universitas Negeri Malang. The results of this study show that EzDubs.ai assists students understand spoken discourse from German videos through Artificial Intellligence (AI) automatic translation. University Students responded positively to the platform, but also complained about the stilted translation, connection problems, and inaccuracy of voice translation. The platform is useful for learning German as well as other foreign languages.